2017
DOI: 10.1016/j.nut.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status as a predictor of duration of mechanical ventilation in critically ill children

Abstract: Malnutrition, based on a variety of anthropometric variables, was associated with the duration of mechanical ventilation in this cohort of critically ill children. Assessment of nutritional status by anthropometry should be performed on admission to the PICU to allow targeted nutritional rehabilitation for the subset of children with existing malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 25 publications
7
39
1
5
Order By: Relevance
“…We have identified no studies in the literature describing this association in critically ill children. Grippa et al 30 observed that upper arm muscle area-for-age besides weight/age and height/age was able to predict the duration of mechanical ventilation in 72 children and adolescents in the PICU, but association with mortality and LOS was not studied. In adults, MUAC was a better mortality predictor compared with BMI in patients with chronic obstructive pulmonary disease, as shown by Soler-Cataluña et al 26 Ravasco et al 5 also observed a higher mortality rate in critically ill adults whose MUAC values were <5th percentile.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified no studies in the literature describing this association in critically ill children. Grippa et al 30 observed that upper arm muscle area-for-age besides weight/age and height/age was able to predict the duration of mechanical ventilation in 72 children and adolescents in the PICU, but association with mortality and LOS was not studied. In adults, MUAC was a better mortality predictor compared with BMI in patients with chronic obstructive pulmonary disease, as shown by Soler-Cataluña et al 26 Ravasco et al 5 also observed a higher mortality rate in critically ill adults whose MUAC values were <5th percentile.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of these and other studies to each other and to the present study are difficult; however, because of the wide variation in their definitions of malnutrition and the outcomes they measured . One advantage of our study is the use of standardized ASPEN definitions of malnutrition severity, which are derived from expert consensus, conform to World Health Organization (WHO) standard growth curves, and have been used in several patient populations, including critically ill children . Moreover, use of standardized malnutrition definitions allows for appropriate comparisons within groups over time and with other studies utilizing the same methodology .…”
Section: Discussionmentioning
confidence: 99%
“…5,10,11,13,17,25 One advantage of our study is the use of standardized ASPEN definitions of malnutrition severity, which are derived from expert consensus, conform to World Health Organization (WHO) standard growth curves, and have been used in several patient populations, including critically ill children. [26][27][28] Moreover, use of standardized malnutrition definitions allows for appropriate comparisons within groups over time and with other studies utilizing the same methodology. 21 One controversial aspect of the ASPEN criteria that deserves mention, however, is the qualification for malnutrition based on height-for-age z-score alone.…”
Section: Discussionmentioning
confidence: 99%
“…The 30-day mortality rate was 5.7%, which was related to the lower birth weight, weight, height and WLZ. Several studies have demonstrated that malnourished CHD patients have a longer hospital stay length (25,31). Ross et al (11) in 2017 found that lower WAZ and LAZ have a significant association with postoperative mortality, cardiac arrest, infection, longer mechanical ventilation and ICU stay.…”
Section: Discussionmentioning
confidence: 99%